Analisis Pelaksanaan Administrasi Pelayanan di Bidang Penanaman Modal pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu - Tarmiji Hamid Siregar (LPPM IAI Nasional Laa Roiba Bogor, 2022)
This study aims to describe and analyze the implementation of service administration in the investment sector at the Medan City Investment and One Stop Integrated Service Office. In this study to collect data the author uses library research methods (Library Research). This technique aims to strengthen the facts in comparing the differences or similarities between theory and practice that the author is researching on the problem related to